2008
DOI: 10.1001/jama.300.11.1303
|View full text |Cite
|
Sign up to set email alerts
|

Association of Urinary Bisphenol A Concentration With Medical Disorders and Laboratory Abnormalities in Adults

Abstract: Context Bisphenol A (BPA) is widely used in epoxy resins lining food and beverage containers. Evidence of effects in animals has generated concern over low-level chronic exposures in humans.Objective To examine associations between urinary BPA concentrations and adult health status.Design, Setting, and Participants Cross-sectional analysis of BPA concentrations and health status in the general adult population of the United States, using data from the National Health and Nutrition Examination Survey 2003-2004.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
784
8
29

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,316 publications
(849 citation statements)
references
References 35 publications
28
784
8
29
Order By: Relevance
“…The actions of environmental estrogens in uterus and early life on the function of the islet of Langerhans are still unknown and it is an important area of research to explore. In adult humans, however, epidemiological evidence exist that point to BPA as an important environmental risk factor in the development of type 2 diabetes (Lang et al, 2008). In addition, there are causal links between BPA exposure and insulin resistance (Alonso-Magdalena et al, 2006), alteration of insulin biosynthesis and secretion in β-cells in adult male mice and decrease of adiponectin in human adipocytes (Hugo et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The actions of environmental estrogens in uterus and early life on the function of the islet of Langerhans are still unknown and it is an important area of research to explore. In adult humans, however, epidemiological evidence exist that point to BPA as an important environmental risk factor in the development of type 2 diabetes (Lang et al, 2008). In addition, there are causal links between BPA exposure and insulin resistance (Alonso-Magdalena et al, 2006), alteration of insulin biosynthesis and secretion in β-cells in adult male mice and decrease of adiponectin in human adipocytes (Hugo et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some persistent organic pollutants (POPs) have been reported to be linked to the prevalence of type 2 diabetes and insulin resistance . Remarkably, there exists an epidemiological link between BPA concentration in urine and type 2 diabetes, cardiovascular disease and liver enzyme abnormalities in a representative sample of adult US population (Lang et al, 2008;vom Saal & Myers, 2008).…”
Section: E2 and Bpa Are Equally Effective Through A Non-classical Estmentioning
confidence: 99%
“…In addition, resin-based materials, although more and more popular like composite resins and pit and fissure sealants, have caused concern due to the presence of 2,2-bis(4-hydroxyphenyl)propane (Bisphenol A -BPA) (10). BPA is a plastic used in the fabrication of several other products, including bottles, baby bottles, detergents, food packing and its derivatives, may present hazard to health (11).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that BPA could induce changes in various mechanisms and physiological processes, among which early puberty in females and feminization in male at very low levels (12), high-risk breast and prostate cancer (13), calcium influx induction, which leads to release of prolactin (14), development of hyperglycemia, insulin tolerance and diabetes (15), cardiovascular disease (10), abnormal concentration of Y-glutamyl liver enzymes and alkaline phosphatase (16), according to the switching of the β-pancreatic cells (18), dysfunction of thyroid hormone production (18), increase of reactive oxygen species (19), which are implicated in oxidative stress mechanism and over-regulation of cAMP response element binding protein, which inhibits apoptosis (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation